Morpho-Syntactic Abilities of Unbalanced Bilingual Children: A Closer Look at the Weaker Language - Meir, Natalia (Frontiers in Psychology, 2018)
Previous studies evaluating morpho-syntactic abilities in the Weaker Language of unbalanced bilingual children are scarce; and they bring inconclusive evidence on the nature of the Weaker Language development. The current study looked into morpho-syntactic profiles of bilingual Russian-Hebrew speaking children in the Weaker Language (the Weaker Heritage Language (HL-Russian) and the Weaker Societal Language (SL-Hebrew)) as compared to balanced bilinguals, unbalanced bilinguals in the Dominant Language and bilinguals with Specific Language Impairment (SLI). Four groups of bilingual children aged 5;5-6;5 participated: unbalanced bilinguals with the Weaker HL-Russian and the Dominant SL-Hebrew (HL-weak: n=39), unbalanced bilinguals with the Weaker SL-Hebrew and the Dominant HL-Russian (SL-weak: n=19); balanced bilinguals (BB: n=38), and bilinguals with SLI (biSLI: n=23)). Children`s morpho-syntactic abilities in both languages were investigated using LITMUS (Language Impairment Testing in Multilingual Settings) Sentence Repetition Tasks (based on Marinis and Armon-Lotem, 2015). Quantitative analysis of morpho-syntactic abilities showed that unbalanced bilinguals scored lower in the Weaker Language as compared to balanced bilinguals and unbalanced bilinguals in the Dominant Language, yet, higher than bilinguals with SLI. Error patterns were similar across bilingual groups with TLD and could be traced to cross-linguistic influence. By contrast, error profiles of unbalanced bilinguals in the Weaker Language and bilinguals with SLI bore fundamental differences. Whereas unbalanced bilinguals in the Weaker Language opted for complex structures, relying on the available resources from the Dominant Language; bilinguals with SLI simplified complex syntactic structures. To conclude, the study shows that the Weaker Language of unbalanced bilinguals with TLD develop qualitatively similarly to the languages of balanced bilinguals and the Dominant Language in unbalanced bilinguals, albeit delayed or influenced by the Dominant Language to a larger extent. Conversely, the study brings evidence that linguistic profiles of unbalanced bilinguals with TLD in the Weaker Language and bilinguals with SLI differ, pointing at a deviant pattern of acquisition in children with SLI.